Efeito da Aloe vera no cultivo in vitro e na criopreservação de folículos pré-antrais inclusos no tecido ovariano de bovinos - Costa, Francisco das Chagas (2020)
The objective of this work was to evaluate the effects of the addition of Aloe vera on in vitro culture and on the cryopreservation of pre-antral follicles included in bovines ovarian tissue on the activation and development, viability, morphological integrity, configuration of the extracellular matrix (EC) and mRNA expression for SOD, CAT, PRDX6 and GPX1. The study was carried out in two stages. In step I, in situ cultivation was performed, where the ovarian cortex was divided into fragments of approximately 3x3x1 mm, which were then cultured for 6 days in 24-well plates containing 1 ml of α-MEM+ medium alone or supplemented with different concentrations of Aloe vera (1%, 5%, 10% and 50%). At the end of the cultivation period, the fragments were submitted to histological analysis for morphological evaluation and follicular development, in addition to the EC analysis. In step II, ovarian fragments were cryopreserved by the method of vitrification on a solid surface with only the medium for vitrification alone or with this medium supplemented with the two best concentrations of Aloe vera from step I and thawed after two weeks. After thawing, the vitrified fragments were subjected to the same evaluations performed for fragments cultured in vitro in step I, in addition to the viability analysis using calcein and ethidium homidimer, gene expression for SOD, CAT, PRDX6 and GPX1 and capacity for follicular activation and development after cryopreservation using an in vitro culture for 6 days. Regarding step I, the results showed that treatment with 50% Aloe vera showed better rates of morphologically normal follicles than treatment with 10% Aloe vera. However, better rates of activation and follicular development were observed at a concentration of 10% in comparison with the other concentrations used. In addition, the 10% and 50% concentrations of Aloe vera maintained collagen levels in the tissue similar to the fresh control. Regarding step II, it was observed that the presence of 10% of Aloe vera in the vitrification solution maintained better rates of healthy follicles. In addition, both concentrations tested maintained collagen levels similar to fresh control, increased levels of mRNA for SOD, PRDX6 and GPX1 and significantly higher follicular activation rates than that seen in the group without Aloe vera. In conclusion, the presence of Aloe vera in the in vitro culture medium and in the vitrification solution improves the overall quality of the follicle and ovarian tissue, maintaining viability and promoting follicular activation and development, in addition to greater expression of important associated genes oxidative stress.